Auditory model: effects on learning under blocked and random practice schedules - Han, D.-W.; Shea, C. H. (Research Quarterly for Exercise and Sport, 2008)
An experiment was conducted to determine the impact of an auditory model on blocked, random, and mixed practice schedules of three five-segment timing sequences (relative time constant). We were interested in whether or not the auditory model differentially affected the learning of relative and absolute timing under blocked and random practice. Participants (N = 80) were randomly assigned to one of eight practice conditions, which differed in practice schedule (blocked-blocked, blocked-random, random-blocked, random-random) and auditory model (no model, model). The results indicated that the auditory model enhanced relative timing performance on the delayed retention test regardless of the practice schedule, but it did not influence the learning of absolute timing. Blocked-blocked and blocked-random practice conditions resulted in enhanced relative timing retention performance relative to random-blocked and random-random practice schedules. Random-random and blocked-random practice schedules resulted in better absolute timing than blocked-blocked or random-blocked practice, regardless of the presence or absence of an auditory model during acquisition. Thus, considering both relative and absolute timing, the blocked-random practice condition resulted in overall learning superior to the other practice schedules. The results also suggest that an auditory model produces an added effect on learning relative timing regardless of the practice schedule, but it does not influence the learning of absolute timing.